2013
DOI: 10.2144/000114002
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of miRNA Isolation and RT-qPCR Technologies and their Effects on Quantification Accuracy and Repeatability

Abstract: MicroRNAs (miRNAs) are short (~22 nucleotides), non-coding RNA molecules that post-transcriptionally regulate gene expression. As the miRNA field is still in its relative infancy, there is currently a lack of consensus regarding optimal methodologies for miRNA quantification, data analysis and data standardization. To investigate miRNA measurement we selected a panel of both synthetic miRNA spikes and endogenous miRNAs to evaluate assay performance, copy number estimation, and relative quantification. We compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
89
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(92 citation statements)
references
References 47 publications
2
89
0
Order By: Relevance
“…MiRNA quantification by both methods, however, showed difference in variability that impact miRNA measurements, and therefore quantification is influenced by the choice of assay methodology. Thus, the method used for quantification must be considered when interpreting analyses of PCR results [77][78][79][80].…”
Section: Current Methods For Colon Cancer Screeningmentioning
confidence: 99%
“…MiRNA quantification by both methods, however, showed difference in variability that impact miRNA measurements, and therefore quantification is influenced by the choice of assay methodology. Thus, the method used for quantification must be considered when interpreting analyses of PCR results [77][78][79][80].…”
Section: Current Methods For Colon Cancer Screeningmentioning
confidence: 99%
“…For 67 commonly detectable miRNAs in plasma and serum, a low correlation between the two qRT-PCR methods was found. A second study revealed that the two methods yielded significantly different copy number estimations of some miRNAs, even though the efficiency appears to be similar [73]. To the best of our knowledge, at present, no consensus has been reached regarding which assay should be preferentially used.…”
Section: Current Limits To the Use Of Circulating Mirnas In Clinical mentioning
confidence: 97%
“…Other assay (the miRCury LNA Universal RT PCR) involves the poly(A)tailing of mature miRNAs and the subsequent use of a poly (T) reverse transcription primer containing a 3' degenerate anchor and a 5' universal tag to generate cDNA for amplification by SYBR Green qPCR using miRNA-specific forward and reverse primers containing locked nucleic acids (LNAs). The primers are commercially available or easy to design on the basis of the sequence identified by the microarray (46).…”
Section: Biogenesismentioning
confidence: 99%